Biomaterials : principles and practices - Wong, Joyce Y.; Bronzino, Joseph D; Peterson, Donald R. (CRC Press, 2013)
"Most current applications of biomaterials involve structural functions, even in those organs and systems which are not primarily structural in their nature, or very simple chemical or electrical functions. Complex chemical functions such as those of the liver and complex electrical or electrochemical functions such as those of the brain and sense organs cannot be carried out by biomaterials at this time. With these basic concepts in mind, this book focuses on biomaterials consisting of different materials such as metallic, ceramic, polymeric, and composite. It highlights the impact of recent advances in the area of nano- and microtechnology on biomaterial design"--